A coupling for success: Controlled growth of Co/CoOx nanoshoots on perovskite mesoporous nanofibres as high-performance trifunctional electrocatalysts in alkaline condition. (February 2017) - Hua, Bin; Li, Meng; Sun, Yi-Fei; Zhang, Ya-Qian; Yan, Ning; Chen, Jian; Thundat, Thomas; Li, Jian; Luo, Jing-Li
Abstract: The high cost and poor durability of noble metal electrocatalysts for bifunctional oxygen catalysis and water splitting have hindered the widespread adoption of many energy storage and conversion technologies. In order for these technologies to be more competitive, advanced electrocatalysts with much higher performance and lower cost are required. The structural and chemical flexibilities of perovskite oxides enable them to be easily modified for diverse catalytic applications. Here we combine three strategies to develop a high-performance trifunctional perovskite electrocatalysts: 1) design a mesoporous fibrous nanostructure; 2) couple a dual functional system; and 3) engineer surface oxygen vacancies. The obtained nanomaterial shows promise to catalyze ORR/OER/HER in alkaline conditions, implying that optimization of the internal/external structure via engineering the defect chemistry of a complex perovskite catalyst would be helpful in advancing its catalytic activity. This protocol discloses an exciting new opportunity to design multifunctional perovskite catalysts for energy storage and conversion. Graphical abstract: The synergistic coupling of perovskites with metal/metal-oxides is a high-performance trifunctional electrocatalyst for ORR/OER/HER. Highlights: The defect chemistry engineering of perovskites enabling ORR/OER/HER catalysis. The coupling of perovskites with Co/CoOx towards synergistic electrocatalysis. The design of microstructure is helpful in advancing the performance of perovskite.